2021
DOI: 10.1088/1572-9494/ac02b6
|View full text |Cite
|
Sign up to set email alerts
|

Electron Acceleration by a radially polarised cosh-Gaussian laser beam in vacuum

Abstract: In this paper, a radially polarised cosh-Gaussian laser beam (CGLB) is used to study the electron acceleration produced in vacuum. A highly energetic electron beam can be achieved by a CGLB, even with comparatively low-powered lasers. The properties of a CGLB cause it to focus earlier, over a shorter duration than a Gaussian laser beam, which makes it suitable for obtaining high energies over small durations. It is found that the energy gained by the electrons strongly depends upon the decentering parameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Invention of short laser pulses Wake field acceleration by using plasma medium is also a promising method which helps particles to achieve more energy compared to RF based accelerators [10,13,14]. Researchers shows the dynamics of electron by applying azimuthal magnetic field in vacuum for circularly polarised and linear laser pulses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Invention of short laser pulses Wake field acceleration by using plasma medium is also a promising method which helps particles to achieve more energy compared to RF based accelerators [10,13,14]. Researchers shows the dynamics of electron by applying azimuthal magnetic field in vacuum for circularly polarised and linear laser pulses [15].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] SRS is a noteworthy issue that is not limited to the Inertial Confinement Fusion (ICF) procedure alone. Additionally, this phenomenon poses a noteworthy constraint in various high-power interactions between lasers and plasmas, such as electron acceleration, particularly laser wakefield and beat wave accelerators and THz radiation generation [5][6][7][8][9][10][11][12][13]. Within forward Raman scattering, an electron plasma wave is produced, characterized by an elevated phase velocity, propelling charged particles to exceptionally elevated energies.…”
Section: Introductionmentioning
confidence: 99%
“…In a laser-heated capillary discharge waveguide, a relativistic strong laser pulse with a peak power of 0.85 PW is employed to produce electron beams with energies up to 7.8 GeV [16]. Laser propagation characteristics plays an important role in electron energy gain while acceleration in vacuum and ion channel [17][18][19][20]. The characteristics of a radially polarized (RP) laser pulse, such as the presence of a stronger longitudinal electric field than the transverse field, are employed to improve electron trapping and acceleration to energies of the order of GeV [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al experimentally demonstrated that milli joule laser pulses produce electron bunches of MeV energy with low divergence and provided a model for electron acceleration by RP tightly focused laser pulses in micro-channel [19]. The RP cosh-Gaussian (ChG) laser is used to explore electron acceleration in vacuum [20]. The decentered parameter dependent ChG laser can create highly energetic electron even with low power lasers.…”
Section: Introductionmentioning
confidence: 99%